Strengthening Organizational Culture, Work Discipline, and Job Satisfaction to Build Civil Servants’ Organizational Citizenship Behavior - Muhammad Tafsir; Syamsul Alam; Nurlaely Razak; Hasyim Mochtar; Marwah Yusuf; Heslina Heslina; Abdul Malik (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the effects of organizational culture and work discipline on Organizational Citizenship Behavior (OCB), with job satisfaction as a mediating variable among civil servants (Aparatur Sipil Negara) in Makassar City Government institutions. Methodology: A cross-sectional quantitative design was used. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Purposive sampling was employed, involving 77 respondents in total. Results: The findings show that organizational culture and work discipline significantly and positively affect job satisfaction but do not directly influence the OCB. Job satisfaction significantly and positively affected OCB and served as a significant mediator between organizational culture, work discipline, and OCB. Thus, organizational factors influence OCB primarily through an employee’s job satisfaction. Conclusion: Job satisfaction is a crucial psychological mechanism linking organizational culture and work discipline to OCB among civil servants. Limitations: The cross-sectional design limits causal inference, and the single-region scope restricts the generalizability of the findings. Contribution: This study reinforces the role of job satisfaction as a mediator in public sector organizational behavior research and offers practical implications for improving OCB among civil servants through better organizational culture and fair work discipline.